An ideal bathroom - its equipment and care - McKeen, Ethel Olive (My University, 1908)
Introduction: Pride in ones home lies at the very root of the domestic instinct, as with the human heart, cleanliness accompanies pure morals. The influence of home on the family is determined to be good or bad as a result of the environment of details.
Citation: McKeen, Ethel Olive. An ideal bathroom - its equipment and care. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Bathrooms; Architecture; Design; Domestic Science; Graduating theses; Senior theses; Theses